2009
DOI: 10.1149/1.3104642
|View full text |Cite
|
Sign up to set email alerts
|

Electrolysis of (CH3)4NF•5HF Melt with Boron-doped Diamond Anode

Abstract: Since a boron-doped diamond (BDD) electrode is able to be used as an anode in the (CH3)4NF•mHF melt, the performance of BDD anode for electrolytic production of perfluorotrimethylamine [(CF3)3N] was investigated in the melt of (CH3)4NF•5.0HF by galvanostatic electrolysis at 20, 40, 60 and 100 mA•cm−2. The anode gas was analyzed quantatively by gas chromatography-mass spectroscopy. Also, the surface of BDD electrode before and after electrolysis was analyzed by XRD and Raman spectroscopy and was observed by S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Regarding the durability of anode materials, it is known that Pt anodes dissolve into MeCN and methanol during anodic oxidation, [33] while BDD anodes are mechanically and chemically stable enough even after repeated use in these solvents. Mizuno also reported that BDD anode surface structure was maintained during electrolysis in Me 4 NF-5HF melt producing (CF 3 ) 3 N. 34…”
Section: Anodementioning
confidence: 97%
“…Regarding the durability of anode materials, it is known that Pt anodes dissolve into MeCN and methanol during anodic oxidation, [33] while BDD anodes are mechanically and chemically stable enough even after repeated use in these solvents. Mizuno also reported that BDD anode surface structure was maintained during electrolysis in Me 4 NF-5HF melt producing (CF 3 ) 3 N. 34…”
Section: Anodementioning
confidence: 97%